Maintaining Relationships Is Critical in Network's Success - Alison Gilchrist (HealthcarePapers, 2006)
As the authors of the lead paper recognize, networks have become an increasingly popular form of organizing, both in the delivery of public services and within political arenas. A network is an arrangement of individuals and/or organizations that are linked through connections that range from informal relationships to formally agreed protocols. Networks have proved useful in addressing complex and intractable problems that require a holistic approach to identifying and implementing long-term solutions. They succeed in situations where hierarchies and "silo-based" systems have failed, and are particularly valuable in facilitating the transfer of resources and knowledge across sectoral and organizational boundaries.